Longitudinal Study on Pre- and Post-Operation CT Imaging for Predicting Pedicle Screw Loosening in Patients with Lumbar Degenerative Disease - Zhang Q; Zhao F; Zhang Y; Gong X (Therapeutics and Clinical Risk Management, 2024)
Qian Zhang,1– 3,* Fanfan Zhao,2,* Yu Zhang,3 Xiangyang Gong1,2 1Medical College of Soochow University, Suzhou, People’s Republic of China; 2Department of Radiology, Zhejiang Provincial People’s Hospital (Affiliated People’s Hospital), Hangzhou Medical College, Hangzhou, People’s Republic of China; 3Department of Radiology, The 901st Hospital of the Joint Logistics Support Force of PLA, Hefei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiangyang Gong, Department of Radiology, Zhejiang Provincial People’s Hospital, (Affiliated People’s Hospital), Hangzhou, People’s Republic of China, Tel/Fax +86 57187666666, Email cjr.gxy@hotmail.comPurpose: We conducted a longitudinal study to examine the predictive role of risk factors in the occurrence of pedicle screw loosening, assessed through pre- and post-operative computed tomography (CT) scans.Methods: A total of 103 patients with degenerative lumbar disease who had undergone L4/5 pedicle screw fixation (involving 412 screws) were included in this study. They were subsequently categorized into two groups—the “loosening group” and the “non-loosening group”. The axial and sagittal angles of the screw trajectory in pre- and post-operative CT images were measured, and the deviation angles were computed. Additionally, measurements were taken of the Hounsfield unit (HU) within the screw entry point area, the pedicle, and the vertebral body in preoperative CT images. Logistic regression analysis was employed to ascertain the risk factors influencing the occurrence of screw loosening.Results: Elderly patients who experienced screw loosening tended to have bilateral screw issues at the L5 level (p < 0.005). The HU of the pedicle (p < 0.001), age (p < 0.001), and the axial deviation angle (p = 0.014) were identified as independent factors predicting screw loosening. Additionally, when HU of the pedicle < 126.5 or age ≥ 53.5 years, the axial deviation angle was found to be smaller in the group experiencing screw loosening (p = 0.018 and p = 0.019).Conclusion: Loosening of screws positioned at L5 was found to be more prevalent in elderly patients, particularly exhibiting a bilateral occurrence. Independent predictors of this phenomenon included a low HU value in the pedicle, advanced age in patients, and a substantial axial deviation angle. In the case of elderly patients with a low HU value in the pedicle, a reduced axial surgical deflection was necessitated to prevent the occurrence of screw loosening.Keywords: computed tomography, lumbar degenerative diseases, Hounsfield unit, pedicle screw loosening, position deviation value